Gonadal soma controls ovarian follicle proliferation through Gsdf in zebrafish. Issue 11 (25th September 2017) - Yan, Yi‐Lin; Desvignes, Thomas; Bremiller, Ruth; Wilson, Catherine; Dillon, Danielle; High, Samantha; Draper, Bruce; Buck, Charles Loren; Postlethwait, John
Abstract : Background: Aberrant signaling between germ cells and somatic cells can lead to reproductive disease and depends on diffusible signals, including transforming growth factor‐beta (TGFB) ‐family proteins. The TGFB‐family protein Gsdf (gonadal soma derived factor) controls sex determination in some fish and is a candidate for mediating germ cell/soma signaling.Results: Zebrafish expressed gsdf in somatic cells of bipotential gonads and expression continued in ovarian granulosa cells and testicular Sertoli cells. Homozygous gsdf knockout mutants delayed leaving the bipotential gonad state, but then became a male or a female. Mutant females ovulated a few oocytes, then became sterile, accumulating immature follicles. Female mutants stored excess lipid and down‐regulated aromatase, gata4, insulin receptor, estrogen receptor, and genes for lipid metabolism, vitellogenin, and steroid biosynthesis. Mutant females contained less estrogen and more androgen than wild‐types. Mutant males were fertile. Genomic analysis suggests that Gsdf, Bmp15, and Gdf9, originated as paralogs in vertebrate genome duplication events.Conclusions: In zebrafish, gsdf regulates ovarian follicle maturation and expression of genes for steroid biosynthesis, obesity, diabetes, and female fertility, leading to ovarian and extra‐ovarian phenotypes that mimic human polycystic ovarian syndrome (PCOS), suggesting a role for a related TGFB signaling molecule in the etiology of PCOS. Developmental Dynamics 246:925–945, 2017 . © 2017 Wiley Periodicals, Inc. Key Findings: In zebrafish, the TGFB factor gsdf is expressed in gonadal somatic cells before the time of sex determination, and expression continues in granulosa and Sertoli cells. Zebrafish gsdf mutant females ovulate only a few oocytes, then become sterile as they accumulate hundreds of immature follicles. Mutant fish achieve greater mass and accumulate more lipid than wild types. Female mutants down-regulate genes for granulosa cells, lipid and insulin pathways, brain-derived reproductive hormones, and up-regulate androgen. Male gsdf mutants have normal fertility. Gsdf, Gdf9, and Bmp15 arose as paralogs in the vertebrate genome duplication events. Zebrafish gsdf mutants mimic the ovulation failure, young oocyte accumulation, hyperandrogenism, obesity, and insulin-related phenotypes of human polycystic ovarian syndrome (PCOS). Zebrafish gsdf mutants provide a model for human PCOS disease.